Ethics framework and recommendations to support capabilities of people with intellectual and developmental disabilities during pandemics. Issue 1 (25th February 2022) - Sullivan, William F.; Björne, Petra; Heng, John; Northway, Ruth
Abstract: A growing body of knowledge highlights the negative impact of the COVID‐19 pandemic on the health and well‐being of many people with intellectual and developmental disabilities (IDDs) and their caregivers. The underlying reasons are not only due to biomedical factors but also ethical issues. They stem from longstanding and pervasive structural injustices and negative social attitudes that continue to devalue people with IDD and that underlie certain clinical decisions and frameworks for public‐health policies during this pandemic. Unless these fundamental ethical shortcomings are addressed, pandemic responses will continue to undermine the human rights and well‐being of people with IDD. This paper proposes an ethics framing for policy and practices regarding clinical care and public health based on Martha Nussbaum's approach to Capability Theory. Such a framework can reorient healthcare professionals and healthcare systems to support the capabilities of people with IDD to protect, recover, and promote health and well‐being. It could be applied during this pandemic and in planning for future pandemics. The paper presents some practical recommendations that follow from applying this framework.